Testing the availability of comprehensive quality management principles and their relationship to project success - experimental research for a number of projects of the consulting office / University of Karbala - Nidaa Saleh Mahdi (Iraqi Journal for Administrative Sciences, 2025)
The research aims currenttotestthe availability ofthe principles oftotal quality managementin a sample ofprojectsAdvisory Officeat the University ofKarbala,as well as thediagnosis ofthe relationshipbetween the application ofthe principles oftotal quality managementandproject success, as well as "a test variationthree projectsin the application ofthe principles oftotal quality management toachievethe success ofits projects.For the purposes of scientificresearchselecteda random sample of(55)people"working invariouslevels of management, technicalandoperationalinthree projects. Thequestionnaireusedas atoolheadfordatacollectioneffort, "including hypothesis testingandverification of thecorrelationsandthecontrastbetweentheprojectsto reachresults usingstatisticalsoftware(Spss). The research founda set ofconclusions, including the power ofcorrelationandthe moralof the principles oftotal quality managementandsuccess of the project, as well as "all provehypothesesnothingnessthat there is nosignificant differences betweenthe three projectsfor bothvariables(the principles of total quality managementand the success ofthe project)by project typeand duration ofimplementation, whileaccepted thealternative hypothesisthat therearesignificantdifferencesbytypeofsector.